2008
DOI: 10.1080/02701367.2008.10599501
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Long-Term Exercise Adherence in Women Who Complete a Structured Exercise Program

Abstract: The purpose of this study was to qualitatively examine factors related to physical activity adherence to understand why women continue to participate in long-term exercise after completing a structured exercise program. Data were collected from focus groups, interviews, and e-mails, and analysis used grounded theory. The central category related to physical activity adherence was self-worth. Motivation, activity enjoyment, priorities, body image, ability to access support, and self-regulation skills had an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
93
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 43 publications
9
93
1
1
Order By: Relevance
“…To enhance opportunities for physiological and neuromusculoskeletal change, exercise protocols should follow the principles of "overload" (e.g., speed, performance time, frequency, progressive difficulty) with adaptation to individual signs and symptoms and individual preferences [66,67]. Unfortunately, the effects of exercise are transient unless continued [68][69][70] wireless monitoring of mobility (e.g., pedometer, sleep, medication management) with occasional face to face visits for a review of exercises, may help with compliance along with the convenience of the fitness center location, efficiency of performance, time of day, safety, potential group support and positive feedback [70][71].…”
Section: Characteristics Of Equipment/work Out* Nusteptm-vasper Altergrmentioning
confidence: 99%
“…To enhance opportunities for physiological and neuromusculoskeletal change, exercise protocols should follow the principles of "overload" (e.g., speed, performance time, frequency, progressive difficulty) with adaptation to individual signs and symptoms and individual preferences [66,67]. Unfortunately, the effects of exercise are transient unless continued [68][69][70] wireless monitoring of mobility (e.g., pedometer, sleep, medication management) with occasional face to face visits for a review of exercises, may help with compliance along with the convenience of the fitness center location, efficiency of performance, time of day, safety, potential group support and positive feedback [70][71].…”
Section: Characteristics Of Equipment/work Out* Nusteptm-vasper Altergrmentioning
confidence: 99%
“…For example, measuring Emotional SW as it relates to PA would include items about a woman prioritizing herself over others to participate in PA. Previous research (Huberty, Ransdell, Sidman, Flohr, Shultz, Grosshans et al, 2008b) has found that women tend to prioritize themselves lower than others, which may negatively impact their ability to participate in PA as well as their self-worth. Having the ability to measure that dimension is important because it is possible that Emotional SW is a more powerful mediator of PA and Global SW in women than in men, but questionnaires are needed to measure that dimension.…”
Section: Introductionmentioning
confidence: 99%
“…While the motivational climate research has been more systematically applied to sport and physical education settings (e.g., Iwasaki & Fry, 2013;Papaioannou, Marsh, & Theodorakis, 2004;Wang, Liu, Chatzisarantis, & Lim, 2010), a growing number of researchers have argued for its application to extend to exercise and fitness settings as well (Brown & Fry, 2014a;Hogue et al, 2013;Huddleston et al, 2012;Moore & Fry, 2014). Researchers have argued that staff in fitness settings are similar to physical education teachers and coaches in their opportunities to work with participants-thereby influencing members' future commitment to physical activity Huberty et al, 2008). Fitness center staff can use language and actions that help individuals focus on their own effort and improvement and deemphasize normative standards Huberty et al, 2008).…”
Section: Psychometric Properties Of the Abbreviated Perceived Motivatmentioning
confidence: 99%
“…Researchers have argued that staff in fitness settings are similar to physical education teachers and coaches in their opportunities to work with participants-thereby influencing members' future commitment to physical activity Huberty et al, 2008). Fitness center staff can use language and actions that help individuals focus on their own effort and improvement and deemphasize normative standards Huberty et al, 2008). Brown and Fry (2014) found that fitness facility members' perceptions of the staff's positive and supportive behaviors correlated with the members' perceptions of the facility's climate as caring and taskinvolving.…”
Section: Psychometric Properties Of the Abbreviated Perceived Motivatmentioning
confidence: 99%